2013
DOI: 10.1177/1476718x13497354
|View full text |Cite
|
Sign up to set email alerts
|

“I Know How You Feel”: Preschoolers’ emotion knowledge contributes to early school success

Abstract: Differences in emotion knowledge by children's age, gender, and socioeconomic risk status, as well as associations of emotion knowledge with executive control, social competence, and early classroom adjustment, were investigated. On emotion knowledge, 4-and 5-year-olds scored higher than 3-yearolds, with girls showing this effect more strongly. Socioeconomic risk status and emotion knowledge were negatively related. Furthermore, executive control was found to contribute to variance in emotion knowledge. Even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 30 publications
5
69
0
13
Order By: Relevance
“…In sum, identification of such indirect effects is a strength of this model. Further, as in Denham et al (, ), emotion knowledge predicted emotionally regulated/prosocial behaviour (see also Denham et al, in press‐a; Schultz et al, ). In contrast, emotion knowledge did not predict early school success; however, its contribution to emotionally regulated/prosocial behaviour is one that has been theoretically suggested for decades (e.g., Denham, ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In sum, identification of such indirect effects is a strength of this model. Further, as in Denham et al (, ), emotion knowledge predicted emotionally regulated/prosocial behaviour (see also Denham et al, in press‐a; Schultz et al, ). In contrast, emotion knowledge did not predict early school success; however, its contribution to emotionally regulated/prosocial behaviour is one that has been theoretically suggested for decades (e.g., Denham, ).…”
Section: Discussionmentioning
confidence: 59%
“…Indirect, mediational pathways will also be explored; we would expect that the social–emotional competencies we consider more foundational might have, along with direct effects, indirect contributions to classroom adjustment and academic readiness via more clearly ‘applied skills’ (see Figure ), but little or no research has explored such linkages. In one of the few studies examining how aspects of SEL enumerated here may mediate one another in contributing to early school success, Denham et al () found that emotionally negative/aggressive behaviour mediated relations between aspects of emotion knowledge, as well as HEC, and both concurrent and later school adjustment (see also Denham, Bassett, Brown, Way, & Steed, in press‐a, for the indirect contribution of executive control to social competence via emotion knowledge).…”
Section: A Theory Of Social–emotional Learningmentioning
confidence: 87%
“…Specifically, social play is related to higher levels of overall social competence and positive psychosocial adjustment (Coolahan, Fantuzzo, Mendez, & McDermott, ; Howes, Rubin, Ross, & French, ; Parker, Rubin, Erath, Wojslawowicz, & Buskirk, ). Further, positive peer interactions in preschool and beyond are related to better school adjustment and academic competence (Baker, ; Buhs & Ladd, ; Denham, Bassett, Brown, Way, & Steed, ; DeRosier & Lloyd, ). In light of these important outcomes, the purpose of the current study was to understand the factors that predict children’s engagement in social play and reticent/uninvolved behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous research (Tarr, Launay, Cohen, & Dunbar, ; Valdesolo & DeSteno, ), we hypothesized greater enjoyment of the movement game in the synchrony than in the non‐synchrony condition. It has also been suggested that bodily alignment arising from synchronous movements can enhance empathy (Feldman, ; Valdesolo & DeSteno, ), which strongly predicts children's helping behavior and social bonds with friends (Denham, Bassett, Brown, Way, & Steed, ; Zahn‐Waxler, Radke‐Yarrow, & Brady‐Smith, ). We therefore hypothesized that more helping behavior, mutual smiles, eye contact and empathy would occur following synchronous than non‐synchronous movement.…”
Section: Introductionmentioning
confidence: 99%